Case Report: Rare diffuse giant cell tumor of the tendon sheath in the cervical facet joint - Jiang, Yongliang; Xu, Chongxi; Ma, Junpeng; Luo, Tianyou (Frontiers in Oncology, 2025)
Giant Cell Tumor of the Tendon Sheath (GCTTS) is a rare neoplasm that can exhibit local aggressiveness but is generally benign. GCTTS is commonly classified into two subtypes: localized and diffuse, and rarely affects the axial skeleton. Diagnosing GCTTS in the spine is challenging, and it is associated with localized pain and neurological symptoms. Surgical resection is now the preferred treatment, though recurrence rates remain high. This report describes an exceptionally rare case of rapidly progressive and extensively invasive diffuse GCTTS affecting the lateral joints, surrounding vasculature, and nerves of the cervical spine. We also review the clinical presentation, imaging characteristics, and therapeutic outcomes of spinal GCTTS to enhance understanding and awareness of this rare pathology.